The report (Journal of Parents and Teachers, 2023)
Education is a process that is updated and improved over time. Therefore, it is necessary to reflect on it and one way to do it is through reports. In this article we talk about the use of them, indicating the appropriate way to use them and which are the data that are collected in them.
Keywords: report; evaluation; education